P203 The 'lexicon of love': understanding types of relationships as primary contexts of STI transmission. (8th June 2017) - Pothoulaki, Maria; Vojt, Gabriele; Mapp, Fiona; Woode-Owusu, Melvina; Flowers, Paul; Estcourt, Claudia; Mercer, Cath; Saunders, John; Wayal, Sonali; Cassell, Jackie; Nandwani, Rak; Symonds, Merle
Abstract : Introduction: Social contextual factors are often not taken into account when examining STI transmission. Understanding relationship types is central to targeting sexual health services, such as partner notification. This study examines the public's understandings of the language used to describe different types of partners and sexual relationships. Methods: A qualitative study, involving six focus groups was conducted in Scotland and England. Purposive sampling recruited 38 participants, including young heterosexuals (n=22) and gay men and other men who have sex with men (n=16). A semi-structured topic guide was used to facilitate the discussion, which included interactive tasks. An integrative thematic analytic approach was adopted by synthesising both textual data and the data derived from the interactive tasks. Results: Findings highlighted the diverse ways that relationships are understood and the fluid nature of partner types. Themes illustrated the importance of a range of contextual factors such as the variable nature of sexual relationships and key differences in their affective elements, the importance of peer context, social identities and developmental trajectories and the role of online communication in developing and shaping sexual networks and partnership formation. Discussion: Social identities and people's historical and geographic context 'shape' the way people talk about relationships. Fluidity and contextualisation are two key elements to be taken into consideration in understanding the language and terms used to describe relationships. From a public health perspective, understanding relationship types can unveil pathways to understand transmission patterns of STIs and provide more effective sexual health services.